TEORI BATAS DALAM PENAFSIRAN AURAT PEREMPUAN: TELAAH PEMIKIRAN MUHAMMAD SYAHRUR - Salahuddin Harahap; Nida Holita Nasution; Anisyah Khoiroh Rangkuti; Maulana Muhammad Noer (Wahdatul Ulum Institute, 2026)
This study examines Muhammad Syahrur's deconstructive thinking in response to the deadlock in Islamic interpretation in the modern era. By combining scientific logic and linguistics, Syahrur introduces the “Theory of Limits” as a new tool for understanding the legal verses in the Qur'an more dynamically. The main focus of this paper is to examine how this theory is applied to the verses concerning women's genitals, particularly in the reinterpretation of the term al-juyub. Through this contemporary reading, Syahrur offers a new perspective that the boundaries of Muslim clothing have a flexible range between minimum and maximum values. The results of the study show that Syahrur's thinking is not merely a free ijtihad, but an intellectual effort to prove that the message of the Qur'an remains relevant and capable of dialogue with the sociocultural realities of the 21st century.